2013
DOI: 10.1073/pnas.1221734110
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a previously undescribed family of sequence-specific DNA-binding domains

Abstract: Sequence-specific DNA-binding proteins are among the most important classes of gene regulatory proteins, controlling changes in transcription that underlie many aspects of biology. In this work, we identify a transcriptional regulator from the human fungal pathogen Candida albicans that binds DNA specifically but has no detectable homology with any previously described DNA-or RNA-binding protein. This protein, named White-Opaque Regulator 3 (Wor3), regulates white-opaque switching, the ability of C. albicans t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(136 citation statements)
references
References 51 publications
5
131
0
Order By: Relevance
“…This contrasts with the relatively less complex TF repertoire of other multicellular lineages, such as Fungi, the brown algae E. siliculosus, or even the red alga Chondrus crispus (51). There exists the possibility that our analysis has missed as-yet-undescribed TFs that are unique to those lineages, as TFs that are restricted to small clades may be more prevalent than expected (52). In any case, fungi and brown and red algae did not expand their repertoire of paneukaryotic TFs (Homeoboxes, bHLH, and bZIPs) nor their protein domain architectures, in contrast to embryophytes or metazoans.…”
Section: Metazoa and Embryophyta Have The Richer Tfome Among Eukaryotesmentioning
confidence: 79%
“…This contrasts with the relatively less complex TF repertoire of other multicellular lineages, such as Fungi, the brown algae E. siliculosus, or even the red alga Chondrus crispus (51). There exists the possibility that our analysis has missed as-yet-undescribed TFs that are unique to those lineages, as TFs that are restricted to small clades may be more prevalent than expected (52). In any case, fungi and brown and red algae did not expand their repertoire of paneukaryotic TFs (Homeoboxes, bHLH, and bZIPs) nor their protein domain architectures, in contrast to embryophytes or metazoans.…”
Section: Metazoa and Embryophyta Have The Richer Tfome Among Eukaryotesmentioning
confidence: 79%
“…When WOR1 is overexpressed in ras1, pde2, cyr1, tpk1, or tpk2 mutant backgrounds, the opaque state results, showing that Wor1 is the transcriptional effector downstream of the Ras signaling components that regulates the W-O switch (106). Other studies have identified additional transcription factors that control the W-O switch in concert with Wor1, namely, Czf1, Efg1, Wor2 (58, 110), the recently described Wor3 (56), and the mating-type proteins a1 and ␣2 (110) that create the genetic environment required for the W-O switch (Fig. 3E).…”
Section: White-to-opaque Switchingmentioning
confidence: 94%
“…While a direct association with Ras signaling and Czf1, Wor2, or Wor3 has not been described, these transcription factors act in concert in a transcriptional regulatory-feedback loop with Ras-regulated Efg1 and Wor1. Similarly to the complex regulatory circuit that controls biofilm formation, Czf1, Wor1, Wor2, and Wor3 participate in an interlocking regulatory-feedback loop with Efg1 to control the W-O switch (56,110) and thus provide additional support for the idea of fine-tuning of Ras signaling by a complex, context-specific, transcriptional regulatory network that controls phenotypic switching in C. albicans. This transcriptional circuit further is regulated in a complex manner by the regulation of chromatin structure, as the phenotype of the hda1 mutant suggests that the expression of key switch regulators is impacted by Hda1-mediated histone positioning (96).…”
Section: White-to-opaque Switchingmentioning
confidence: 97%
See 1 more Smart Citation
“…In the case of the white-opaque switch, a network of at least six transcription factors (AHR1, CZF1, EFG1, WOR1, WOR2 and WOR3) controls expression of 748 target genes [30, [75][76][77][78]. A detailed analysis of this circuit included ChIP-chip, global transcriptome analysis and mechanically induced trapping of molecular interactions (MITOMI) [75].…”
Section: Investigation Of Chromatin Structure and Transcriptional Regmentioning
confidence: 99%